1995
DOI: 10.1046/j.1432-0436.1995.5930155.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 18 is associated with a subset of older taste cells in the rat

Abstract: All or nearly all intragemmal (elongated) cells of rat taste buds were immunopositive for keratins 7, 8, and 19. In contrast, keratin 18 was detected in 19 +/- 5 cells per taste bud (mean +/- sd), or about 25% of the intragemmal cells. During taste bud development keratins 7, 8, and 19 were evident initially in polygonal cells and later in elongated taste cells. Keratin 8 appeared in vallate taste cells at P0 (postnatal day 0), followed by keratins 7 and 19 at P1, and keratin 18 at P2-P3. Keratin 18 was always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
4
36
1
Order By: Relevance
“…Most recently, Okubo [52] have shown that cells within taste buds arise from K14-expressing basal keratinocytes, which sit along the basement membrane of the lingual epithelium, including that of taste papillae. Taste cells within buds do not express K14, but rather express cytokeratin 8 [52,64,65]. In our studies, while BMP4-ß-gal perigemmal cells are located in a position consistent with that of proposed progenitors and many of BMP4 cells were also K14 positive, we could find no evidence that these cells are actively dividing, via both BrdU birthdating and immunostaining for known markers of proliferation.…”
Section: Discussioncontrasting
confidence: 54%
“…Most recently, Okubo [52] have shown that cells within taste buds arise from K14-expressing basal keratinocytes, which sit along the basement membrane of the lingual epithelium, including that of taste papillae. Taste cells within buds do not express K14, but rather express cytokeratin 8 [52,64,65]. In our studies, while BMP4-ß-gal perigemmal cells are located in a position consistent with that of proposed progenitors and many of BMP4 cells were also K14 positive, we could find no evidence that these cells are actively dividing, via both BrdU birthdating and immunostaining for known markers of proliferation.…”
Section: Discussioncontrasting
confidence: 54%
“…When it is activated by stress, p53 characteristically functions to stall cell division. However, p53 in mouse tongue cannot be functioning to stall cell division, because p53 is restricted to intragemmal cells that do not divide (Farbman, 1980;Zhang et al, 1995). We conclude that,…”
Section: Implications Of P53 Expression In Postmitotic Taste Cellsmentioning
confidence: 76%
“…1H). Additionally, we compared the expression of cytokeratin 8 (K8; Krt8 -Mouse Genome Informatics), a marker of immature taste bud cells (Mbiene and Roberts, 2003;Zhang et al, 1995). At E18.5, K8…”
Section: Resultsmentioning
confidence: 99%